Development of Attentional Skills Training for Operators of Unmanned Aerial Systems. (November 2019) - Sebok, Angelia; Walsh, Matthew; Wickens, Christopher; Andre, Terence; Kreischer, Noah; Pei, Lucy; Bowens, Laticia; Landsberg, Carla
The operators of unmanned aerial systems (UAS) have multiple screens of information they need to monitor, and numerous interruptions that challenge them in their work. Research on attentional training has revealed that it is possible to train operators to improve their visual scanning, prioritization, and interruption management performance. This paper describes the analyses that were conducted to identify the information processing requirements associated with UAS tasks and the integration of findings into a prototype attentional skills training tool. This tool uses adaptive scenario-based training to improve the attentional management skills of UAS sensor operators.